Sunlight-driven photocatalytic degradation of industrial dyes using Withania somnifera decorated MnO2 nanoparticles - Mahi Chaudhary; Chetan Kumar; Sapna Raghav; Medha Panwar; Shivam Pandey; Ritu Painuli (Discover Nano)
Abstract This study presents a unique, fast, and environmentally friendly approach for synthesizing MnO2 nanoparticles (MnO2 NPs) utilizing Withania somnifera (Ashwagandha) extract. The formation of nanoparticles was indicated by a color change from dark purple to dark brown within 10 min and validated through techniques including UV–Vis spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), and Energy Dispersive X-ray (EDX). Bromocresol green and Bromothymol blue were established as standards for assessing the photocatalytic efficiency of the synthesized nanoparticles. The synthesized nanocatalyst exhibited remarkable removal efficiency upon sunlight exposure, achieving 92% for Bromothymol blue and 95% for Bromocresol green within a duration of 1 h. The influence of variables including duration, photocatalyst dosage, and photodegradation kinetics was carefully examined to assess the efficacy of the created photocatalyst. The devised procedure is environmentally benign, facile to execute, and does not necessitate any chemical agents or advanced instrumentation for synthesis. This presents a new opportunity for the advancement of green photocatalysts, which may serve as an outstanding nanomaterial for wastewater clean-up.